2014
DOI: 10.1021/es502674s
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation from Acyclic, Monocyclic, and Polycyclic Alkanes

Abstract: A large number of organic species emitted into the atmosphere contain cycloalkyl groups. While cyclic species are believed to be important secondary organic aerosol (SOA) precursors, the specific role of cyclic moieties (particularly for species with multiple or fused rings) remains uncertain. Here we examine the yields and composition of SOA formed from the reaction of OH with a series of C10 (cyclo)alkanes, with 0-3 rings, in order to better understand the role of multiple cyclic moieties on aerosol formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 35 publications
11
68
3
Order By: Relevance
“…2 (e.g., H/C, O/C) were independent of the NO x levels used in the environmental chambers in the region studied, as has been observed in previous studies (Chhabra et al, 2011). The nitrogen-to-carbon (N/C) ratio ranged from 0.031 to 0.054 for SOA produced in the MIT chamber with added NO x (Hunter et al, 2014) but was not characterized for other measurements shown in Fig. 2.…”
Section: H/c O/c Ratios For Flow Reactor-and Chamber-generated Soasupporting
confidence: 62%
See 3 more Smart Citations
“…2 (e.g., H/C, O/C) were independent of the NO x levels used in the environmental chambers in the region studied, as has been observed in previous studies (Chhabra et al, 2011). The nitrogen-to-carbon (N/C) ratio ranged from 0.031 to 0.054 for SOA produced in the MIT chamber with added NO x (Hunter et al, 2014) but was not characterized for other measurements shown in Fig. 2.…”
Section: H/c O/c Ratios For Flow Reactor-and Chamber-generated Soasupporting
confidence: 62%
“…whereas α-pinene forms SOA with moderate yields (Eddingsaas et al, 2012) and JP-10 forms SOA with mass yields greater than unity (Hunter et al, 2014;Lambe et al, 2012). Yields of alkane SOA do not display a systematic NO x dependence (Loza et al, 2014); thus, to first order we assume different NO x levels between the MIT chamber and PAM reactor do not influence our comparison of measured JP-10 SOA yields.…”
Section: Soa Yields Obtained In the Flow Reactor And Environmental Chmentioning
confidence: 90%
See 2 more Smart Citations
“…Air quality and climate change are major threats to the quality of millions of human lives across the globe (IPCC, 2014;Landrigan et al, 2018). An important scientific component of both topics is the photooxidation chemistry of organic compounds in the atmosphere, which can lead to the formation of ozone and fine particulate matter, both of which can affect the radiative budget of the atmosphere and can harm human health.…”
Section: Introductionmentioning
confidence: 99%